Prevalence and characteristics of anaphylaxis in children at Chaiyaphum hospital - watthanaphanalai, sutatip (Journal of The Department of Medical Services, 2022)
Background : Anaphylaxis is an acute allergic reaction. This is a potentially life-threatening so patients should be receive immediately treatment without any delayed.Objective : This study aimed to estimate the prevalence and clinical characteristics of patients with anaphylaxis at Chaiyaphum Hospital.Method : This study was a descriptive retrospective study at Chaiyaphum Hospital with patients who were evaluated confirm with anaphylaxis, in ages from 0 to 15 years old, from 1st January 2015 to 31st December 2019. Result : The anaphylaxis occurrence rate was 18.6 per 100,000 patients per year. Age-specific rate was highest for ages 11 – 15 years (41.8%). The median and mode duration of onset of anaphylaxis were 60 minutes after exposure . Major causative agents includes food(48.5%) and insect bites/stings(26.2%). The presenting sign and symptoms were skin and cutaneous (96.1%) Respiratory(76.7%) and gastrointestinal(49.5%). All patients received chlopheniramine(CPM) for treatment ,epinephrine was given to 86.4% of the patients.Conclusion : Foods were the most common cause of anaphylaxis. The most common manifestations were skin and cutaneous symptoms and sign. Most of patients were provided treatment with a prescription for epinephrine. So, the basic and implications of diagnostic practices in this disorder warrant further exploration.